The Dynamics of the Sapuh Leger Ritual in Religious Practices - Mahardika, Komang Juni; Putra, I Nyoman Miarta; Ardiyasa, I Nyoman Suka (Research Horizon, 2026)
The Sapuh Leger Ritual is an important Balinese Hindu tradition performed for individuals born during Wuku Wayang, yet its continuity amid social change requires further examination. This study analyzes the ritual’s foundations, explains its implementation process, and examines its impacts on the religious practices of the Hindu community in Bungkulan Village, Sawan District, Buleleng Regency, Bali. This study employed a qualitative research design with a case study approach. Data were collected through participant observation, in-depth interviews, documentation, and literature review, and analyzed using data condensation, data display, and conclusion drawing. The findings show that Sapuh Leger is founded on Hindu teachings, customary law (dresta), and local cultural values reflected in Tri Hita Karana. Its implementation includes preparation, determination of dewasa ayu, ceremonial preparation, panglukatan, Wayang Sapuh Leger performance, and closing prayers. The ritual strengthens religious confidence, psychological reassurance, social solidarity, cultural transmission, and the preservation of local heritage. Despite technical adaptations, its essential religious meanings remain preserved. The study concludes that Sapuh Leger remains a relevant religious, social, and cultural institution through adaptive continuity.